Development of an Interactive E-Module for the Learner Development Course in the Informatics and Computer Engineering Education Study Program at Makassar State University - Mustari S. Lamada; Nurul Mukhlisah Abdal; Sri Reski Amaliah (Journal of Education Psychology and Social Development, 2026)
The availability of interactive digital teaching materials is needed to support the Learner Development course so that learning becomes more effective and accessible. This study evaluated the validity, practicality, and effectiveness of an interactive e-module developed for the Informatics and Computer Engineering Department, Faculty of Engineering, Universitas Negeri Makassar. The study employed a Research and Development (R&D) approach using the 4-D model (define, design, develop, disseminate). Data were collected through expert validation sheets (content and media), a student response questionnaire, and learning achievement tests, and were analyzed using descriptive statistics. The results indicated that the e-module demonstrated very high validity, with scores of 96% from the content expert and 92% from the media expert. Practicality based on student responses reached 90%, categorized as very practical. Effectiveness was evidenced by an 87% learning mastery rate in the very good category, indicating that the e-module effectively supported learning. Therefore, the developed interactive e-module meets the criteria of being valid, practical, and effective, and is feasible for use both in classroom instruction and for independent study.